A systematic review of obesity burden in Saudi Arabia: Prevalence and associated co-morbidities - Hussain A. Al-Omar; Ali Alshehri; Saleh A. Alqahtani; Hana Alabdulkarim; Ali Alrumaih; Mahmoud S. Eldin (Elsevier, 2024)
Introduction: Saudi Arabia has experienced an increasing trend in obesity prevalence in the last three decades; obesity is a significant risk factor for non-communicable diseases, which may cause healthcare and economic burdens. In this systematic review, we aim to explore the obesity prevalence, obesity-related complications (ORCs), and the economic burden of obesity in Saudi Arabia. Methods: Literature searches for relevant local studies across Saudi Arabia spanning 2012 to 2022 were performed in PubMed and EMBASE, along with supplementary searches for relevant congress abstracts. Only studies that discussed obesity prevalence in Saudi Arabia in relation to any gender or age group, the prevalence of ORCs in Saudi Arabia for any gender or age group, and/or the economic burden of obesity and how it impacts the healthcare system in Saudi Arabia, and were published in the English language, were selected for inclusion. No age or gender restrictions were imposed. Results: The prevalence of obesity in Saudi Arabia ranged from 20% to 39% and up to 19.4% among adults and adolescents, respectively. The most reported ORCs were hypertension (67.6%), type 2 diabetes (60.7%), and hypercholesterolaemia (51.3%), and an association between obesity and ORCs was established, showing an increased risk with increasing body mass index. The economic burden of obesity across Saudi Arabia was estimated to be 6.4 billion US dollars (USD) for treatment and management. Conclusion: Obesity affects a substantial proportion of the Saudi general population and is a significant burden on individuals, as demonstrated by the prevalence of ORCs. Multifaceted, short- and long-term approaches involving interventions that operate at multiple levels and target both individuals and communities are urgently needed; there is a particular need for a national strategy and a specific, systems-based policy. Further research will help increase awareness of obesity and its management, which will be crucial for transforming the healthcare system under Vision 2030.